Transnational European television drama : production, genres and audiences /: production, genres and audiences. (2017) - Bondebjerg, Ib; Redvall, Eva Novrup; Helles, Rasmus; Lai, Signe Sophus; Søndergaard, Henrik; Astrupgaard, Cecilie
No abstract available